Physical Capacity and Activity in Patients With Idiopathic Normal Pressure Hydrocephalus - Rydja, Johanna; Kollén, Lena; Ulander, Martin; Tullberg, Mats; Lundin, Fredrik (Frontiers in Neurology, 2022)
Introduction Most patients with idiopathic normal pressure hydrocephalus (iNPH) improve gait after surgery. However, knowledge on physical capacity and activity after shunt surgery is limited. One of the aims of this study was to evaluate the effect of shunt surgery in patients with iNPH on short-distance walking, functional exercise capacity, functional strength, and variables of activity and sleep, 3 and 6 months postoperatively. Another aim was to evaluate the effect of a physical exercise program. Additionally, we studied how changes in short-distance walking were correlated with functional exercise capacity and voluntary walking. Methods In total, 127 patients were consecutively included and randomized to the exercise group (n = 62) or the control group (n = 65). Participants in the exercise group underwent the supervision of a 12-week exercise program. All patients were assessed before surgery, at 3 and 6 months postoperatively with the 10-m walk test (10MWT), the 6-min walk test (6MWT), 30-s chair stand test (30sCST), and with the actigraphic recordings of activity variables measured for a total of 24 h/day for at least 3 days. Results All patients improved at 3 months postoperatively in the 10MWT (p < 0.001), 6MWT (p < 0.001), and 30sCST (p < 0.001). These results were maintained after 6 months. Actigraphic recordings for voluntary walking (steps per minute) were improved and nighttime sleep (%) increased after 6 months (p = 0.01, p = 0.04). There were no significant differences between the exercise group and the control group, except for the postoperative change in the proportion of daytime sleep after 3 months, which was slightly more reduced compared to baseline in the exercise group (p = 0.04). Changes after 3 months in the 10MWT and 6MWT were moderately correlated (ρ= −0.49, p = 0.01) whereas the correlation between the 10MWT and voluntary walking was weak (ρ = −0.34, p = 0.01). Conclusion Shunt surgery improved short-distance walking, functional exercise capacity, functional strength, and voluntary walking. An exercise program did not affect these outcomes. Short-distance walking was weakly correlated with voluntary walking, indicating improved physical capacity does not directly translate to increased physical activity. Further research should address how interventions should be tailored to promote physical activity after shunt surgery. Trial Registration clinicaltrials.gov, Id: NCT02659111.